Quality of life in patients with idiopathic ventricular arrhythmias treated at the Instituto Nacional Cardiovascular - INCOR - Soto-Becerra, Richard (2023)
Objective. To describe the quality of life in patients with idiopathic ventricular arrhythmias treated at the Instituto Nacional Cardiovascular INCOR in Lima -Peru. Materials and methods. Analytical and cross-sectional study of patients with idiopathic ventricular arrhythmias treated by 3D ablation or antiarrhythmic therapy between July 2017 and December 2019 to whom the SF-36 health questionnaire was applied to assess quality of life related to health. Results. Fifty-two patients with idiopathic ventricular arrhythmias were included (34 underwent 3D ablation, and 18 underwent antiarrhythmic therapy only). The percentage of recurrence (14.7% vs. 50%, p=0.01) and adverse effects (0% vs. 22.2%, p=0.011) were lower in the 3D ablation group compared to the antiarrhythmic group. The mean standardized scores obtained from the Spanish version of the Health Survey SF-36v2, applied to the 3D ablation and antiarrhythmic groups were 85.1 vs 68.4 (p<0.001), respectively. Were found statistically significant differences in 6 of the eight components that evaluate health-related quality of life: physical function (96.0 vs. 76.0, p<0.001), physical role (93.4 vs. 61.1, p<0.001), general health (74.5 vs. 47.4, p<0.001), vitality (69.9 vs 54.7, p=0.008), emotional role (92.2 vs. 77.8, p=0.006) and mental health (73.8 vs. 60, p<0.001). Conclusions. Patients with idiopathic ventricular arrhythmias who underwent 3D ablation have a higher mean standardized score for health-related quality of life.